Pengaruh Cita Rasa, Suasana Cafe, Lokasi, Dan Customer Experience Terhadap Loyalitas Pelanggan - Syafiudin, Achmad Imam; Rizal, Mohammad; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The purpose of this research is to find out how big the effect of taste, cafe condition, location and customer experience to customer loyalty. The object of this research is costumer's who have purchased Pipir Lepen Cafe products more than twice of the population. Sampling in this study used a purposive sampling method with a total sample of 95 people. This research used a multiple linear regression model. This research shows that taste, cafe atmosphere, location and customer experience simultaneously influence customer loyalty. Taste has a significant effect on customer loyalty. The atmosphere of the cafe has no significant effect on customer loyalty. Location has no significant effect on customer loyalty. Customer experience has a significant effect on customer loyalty. Keywords: Taste, cafe atmosphere, location, customer experience, customer loyalty